A closed ecological system in a space experiment - Strauch, Sebastian; Schuster, Martin; Lebert, Michael; Richter, Peter; Schmittnägel, Martina; Häder, Donat-Peter (Life in Space for Life on Earth, 2008)
The Russian FOTON-M3 mission, a satellite for midlength experiments in space and recovery afterwards,included a closed artificial ecosystem (OMEGAHAB for Oreochromis Mossambicus-Euglena Gracilis-Aquatic HABitat) with the photosynthetic flagellate Euglena gracilis as oxygen producer and larvae of Oreochromis mossambicus, a Tilapia species, as consumer. During the 12-day orbital flight the algae were observed 10 minutes per day by means of a miniaturized microscope to analyse their swimming behavior. The fishes were also filmed to monitor their development and movement. An identical experiment was carried out as ground control. A data downlink provided the measured temperature values of he space experiment every day to readjust the temperature of the ground reference in order to eliminate the influence of the different temperature on the velocity of the development of the fishes. The system worked very well and confirmed the design in principle. OMEGAHAB was the most successful German experiment of that kind as yet.